Welcoming the New Poor Law: The Bromsgrove Poor Law Union, 1836–1847. (2nd September 2019) - Bradley, Sarah
Abstract : This case study of the Bromsgrove Poor Law Union provides an addition to the literature by examining the early years of a union which welcomed the New Poor Law, and asking how effective it was in implementing it. Other studies have tended to focus on areas of opposition. The union was situated in Worcestershire, on the edge of the Black Country; its nail- and needle-makers and agricultural labourers suffered significant deprivation and ill-health. In 1837, the guardians petitioned Parliament, highlighting properly managed officers, better relief for the needy, and reduced incentives for the idle, as key benefits of the new system. This study finds that, by introducing a proper appointment system, and to a lesser extent by holding officers to account, the union attracted diligent staff. The needy benefited from medical services, moderate success at containing disease, and a relatively humane workhouse, although the latter still acted as a deterrent. Efforts to keep the able-bodied working were inhibited by the system, and Bromsgrove responded pragmatically, continuing to provide out-relief after its abolition, and classifying families as sick wherever possible. Throughout, the degree to which the union sought, obtained and followed the advice and approval of the Poor Law Commission, is striking. Finally, as a new case study, this contributes to the development of a regional approach to the New Poor Law.